Impact of the increasing energy efficiency on the thermal state of medium-power asynchronous motors - Dzenis, Sergii (National Technical University "Kharkiv Polytechnic Institute", 2024)
The proposed work aims to find some interconnections between the temperature state and energy efficiency, which, in turn, may have a positive impact on the global energy –saving problems and their solution. The scientific novelty of the study lies in examining the thermal and electrical fields of the existing motors design; establishing correlation between the thermal state and motor efficiency levels; optimizing the design of the housing and cooling scheme and electromagnetic core on the basis of the research findings.
Keywords: induction motors; asynchronous motors; temperature state; energy-efficient motors; thermal state